Evaluation of the Second – Grade Mathematics Textbook According to International Standards - Amal Abd.A.Abass; Ramla A. Kadhem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study aims to evaluate the second – grade mathematics textbook in accordance with international standards, specifically those set by the National Council of Teachers of Mathematics (NCTM ,2000) , to achieve the aim of the study , the researcher employed the descriptive method by using content analysis . Upon completing the analysis of the textbook content ,the results indicated that the standards were present to a good extent Evaluating the textbook content based on the standards alone is not sufficient , as it does not offer a comprehensive perspective on the organization of the content ,nor does it adequately address the alignment between preceding and subsequent grade levels. While emphasizing these standards may contribute to increased knowledge, it does not necessarily promote a deeper understanding . In addition the standards appear as a lengthy list of subheading grouped under a single main heading which compels curriculum developers to include numerous topics in an attempt to meet these standards . As a result  when teachers cover the content they often neglect the use of appropriate teaching methods and fail to utilize the textbooks effectively and appropriately In order to achieve a balance between the ( NCTM ) standards – encompassing  both content and process standards – the researcher developed a proposed framework for the mathematics textbook content to align with the learners level of understanding and abilities at this stage . the aim was to make comprehension more accessible and enjoyable for students . In developing this proposal the researcher drew upon learning theories of (Piaget  , Bruner , Gagne , and Ausubel ) as well as the developmental characteristics of the targeted age group .DOI: https://doi.org/10.54633/2333-024-056-017